Introduction from management consultant to psychological counsel - McKenna, C (Cambridge University Press, 2017)
Just where do new business ideas come from? As Pankaj Ghemawat’s article, “Evolving Ideas about Business Strategy,” in this issue demonstrates, ideas about business strategy compete within a marketplace that is not simply intellectual but also intensely commercial.1 So intertwined are the academics and the management consultants who have promoted these ideas that Ghemawat employs a classification scheme devised by the consultants in the Boston Consulting Group (BCG) that does not distinguish between the strategy models advanced by consultants and those primarily associated with academics.